Mediastinal A5: a novel artery variant of the pulmonary artery system: a case report - Gang Li; Sheng Gong; Ning Wang; Yong Peng; Xiao-Jun Yao (Journal of Cardiothoracic Surgery)
Abstract Background Variations in the pulmonary artery require increased attention from thoracic surgeons prior to or during lobectomy to avoid severe intraoperative bleeding. Patients with pleural and/or hilar adhesions typically experience more intraoperative bleeding and need longer surgical time. Neglect of the variant pulmonary arteries in the context of strong adhesions may result a fatal bleeding, especially in patients with adhesions caused by pulmonary tuberculosis. Case presentation A 52-year-old man who presented with tuberculoma and strong hilar adhesions of the right upper lobe underwent tri-portal video-assisted thoracoscopic(VATS) lobectomy in our department. In this case, we identified a variant pulmonary artery (mediastinal A5) through three-dimensional computed tomography bronchography and angiography(3D-CTBA). It was an artery that originated from the proximal pulmonary artery trunk, and coursed between the branches of central vein and V1 + 3. The precise identification of this mediastinal A5 artery ensured a safe surgery procedure (Right upper lobectomy) without severe intraoperative bleeding. It is the first report that illustrated a variant mediastinal A5. Misdiagnosis of this variant pulmonary artery may result in severe intraoperative bleeding. 3D-CTBA which could illustrate the variant pulmonary arteries is essential in planning the surgical procedures. Conclusion 3D-CTBA can help illustrating a variant pulmonary artery, and identification of the mediastinal A5 is essential in preforming right upper lobectomy.